Persepsi Guru Pendidikan Jasmani terhadap Implementasi Kurikulum Senam Irama di Sekolah Dasar - Anisah, Anisah; Sulistiyono, Sulistiyono (Jurnal Porkes, 2025)
This study aims to examine physical education teachers' perceptions of the implementation of rhythmic gymnastics curriculum in elementary schools using a qualitative literature review method. This study reviews various research sources that discuss teachers' attitudes, understanding, and challenges in implementing the curriculum in the field. The results of the review of six articles that met the inclusion criteria show that teachers generally recognize the importance of rhythmic gymnastics in developing students' motor skills, coordination, and creativity, as well as contributing positively to children's health and physical development. However, there are significant obstacles in the form of limited teacher competence, which affects their confidence and teaching effectiveness, as well as inadequate supporting facilities and infrastructure in some elementary schools. In addition, differences in the level of experience and training of teachers also affect their readiness and attitude towards the implementation of the rhythmic gymnastics curriculum. The conclusion of this study confirms that improving teacher competence through continuous training and the provision of adequate facilities are strategic steps needed to support optimal implementation of the curriculum. These findings are expected to serve as a reference for policy makers and education practitioners.